A pilot study into the functioning of families with a member who is a hospice patient to determine whether hospice families require family therapy - Evans, Alison (Rhodes University, Faculty of Humanities, Department of Psychology, 1993)
The aim of this pilot study, which was carried out under the auspices of the Grahamstown Hospice, is to evaluate the functioning of families with a terminally ill member, in order to establish whether these families require family therapy. The Family Assessment Device (FAD), based on the McMaster Model of Family Functioning, was used. Data from 20 families was analysed and the extent to which these families constitute a clinical sample is highlighted. In terms of the dimension of General Functioning, 15 families emerged as functioning at a problematic level. Communication emerged as the most dysfunctional of the seven dimensions of the FAD, with 17 families functioning at a problematic level. As a result of these findings it is argued that family therapy should be incorporated into the range of services offered by hospices. Limitations of this study and directions for future research are also discussed.
Keywords: Hospice care; Terminal care; Family psychotherapy